Globalization, market, and money: what roman civilization can teach economic and commercial history - Blázquez, Guillermo Suárez (REVISTA QUAESTIO IURIS, 2022)
Abstract This study undertakes an interdisciplinary assessment of the economic and legal foundations of the ancient world, and in particular, classical Roman civilization. These constitute the guiding principles of business life and the global business world of today. The importance of this original research initiative is to try and provide universal, solid, and timeless scientific pillars and values in order to reliably understand Economic History and the industrial corporate bodies of our interconnected world. Keywords: Freedom of Market, Financial Instruments, Trade, Contracts and Universal Justice, Limited Liability, Industrial Corporations, Capital Markets, Shares and Corporate Debt. Abstract Este estudo realiza uma avaliação interdisciplinar dos fundamentos econômicos e jurídicos do mundo antigo e, em particular, da civilização romana clássica. Estes fundamentos constituem os princípios orientadores da vida empresarial e do mundo empresarial global de hoje. A importância desta iniciativa original de pesquisa é tentar fornecer pilares e valores científicos universais, sólidos e atemporais, a fim de compreender com confiabilidade a História Econômica e os órgãos corporativos industriais de nosso mundo interconectado. Palavras-chave: Liberdade de Mercado, Instrumentos Financeiros, Comércio, Contratos e Justiça Universal, Responsabilidade Limitada, Empresas Industriais, Mercado de Capitais, Ações e Dívida Corporativa.